(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
An Ad hoc network is the network with no fixed infrastructure. There is no central administrator so any node can come and move in and outside of the network in a dynamic manner. This makes it more dynamic and complex which makes it more prone to attacks. They can attack either active or passive. Some effects of malicious nodes are Denial of service, Routing table overflow, Impersonation, Energy consumption, Information disclosure etc. A black hole attack node attracts all packets by falsely claiming a fresh route to the destination node and absorbs them without forwarding them to destination. In this work the effect of Black hole and Gray Hole attack on DSR protocol has been considered. Simulation has been performed on the basis of performance parameters and effect has been analyzed using NS2 simulator.Â